Peran Koperasi Produsen Syariah Pegawai Negeri (KPS-PN) “Budi Luhur” Kantor Kementerian Agama Kabupaten Tapanuli Selatan dalam Pembangunan Ekonomi - Hasibuan, Sofyan Adli (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper examines the strategic role of the Budi Luhur Sharia Producer Cooperative for Civil Servants within the Tapanuli Selatan Regency Ministry of Religious Affairs Office in local economic development. The methodology employed is qualitative, with a descriptive analysis approach, gathering and interpreting information from various relevant literature, internal cooperative documents, and observing operational practices. The study's findings indicate that this cooperative effectively empowers its members through sharia-compliant financing, diversification of productive enterprises (e.g., in the agricultural and services sectors), and provision of market access. The cooperative's presence not only enhances the individual economic well-being of its members through increased income and access to basic necessities but also significantly contributes to strengthening the local community's economy in Tapanuli Selatan by promoting sharia-based economic activities. Furthermore, this cooperative serves as a social safety net and a pillar of solidarity among civil servants. For future role optimization, it is recommended that the Budi Luhur Sharia Producer Cooperative develop innovative sharia products and services, expand strategic partnerships with external parties, and adopt digital technology for management and marketing efficiency, thereby continuously serving as a driving force for sustainable and equitable economic development. Challenges faced include limited capital and adapting to market dynamics. However, with appropriate strategies and support from various stakeholders, the Budi Luhur Sharia Producer Cooperative for Civil Servants has significant potential to continue playing an active role in advancing the regional economy.